The Role of Islamic Religious Education (PAI) Teachers in Instilling the Attitude of Tabayyun Toward Digital Information from the Perspective of Qur'an, Surah Al-Hujurat Verse 6 - Gusmita Zalianti; Rosdialena R (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The widespread dissemination of hoaxes and unverified information in the digital era has become a serious threat to the character development of students, given the high rate of social media usage among Indonesian youth which has reached hundreds of millions of active users. This study aims to describe and analyze the role of Islamic Religious Education (PAI) teachers in instilling the attitude of tabayyun toward digital information from the perspective of QS. Al-Hujurat verse 6. This research employs a library research method with a qualitative descriptive approach through content analysis of relevant primary and secondary literature sources. The findings indicate that PAI teachers hold a conceptual and strategic role encompassing four key functions: as educators who integrate tabayyun values into the curriculum, mentors who cultivate students' critical awareness, motivators who foster the willingness to verify information, and role models (uswatun hasanah) who directly practice Islamic digital ethics. This study concludes that the value of tabayyun in QS. Al-Hujurat verse 6 is highly relevant as a pedagogical foundation in PAI learning in the digital era, as it integrates spiritual, social, and intellectual dimensions that align with digital literacy principles, enabling its internalization to shape a generation of Muslim youth who are critical, selective, and responsible in their digital media conduct.